Identification and Aflatoxin Production of Molds Isolated from Country Cured Hams - Sutic, Marija (1972)
Of 562 molds isolated from country cured hams, 403 isolates were of the genus Penicillium, 121 were Aspergillus, and 36 were Cladosporium, Alternaria, and other genera.